Aplicación de la NIC 36 en el tratamiento del deterioro de la maquinaria y equipo y su incidencia en los estados financieros de la cantera "San Ramón" ubicada en la parroquia Mulaló, período 2018. - Barrera Ruiz, Lizeth Liliana (2020)
The ignorance of the real value that shows the machineries and equipment, related to the wear mainly originated for the forced use of the activities that are making, that simply through the depreciation it is not possible determine, this becomes necessary to apply procedures that allow value the spoilage thereof, these are not simple, it requires of high knowledge, technical and professional beginnings to transparent accounting accounts. For this reason, the present research of degree had as purpose, the application of the procedure of deterioration of the machineries and equipment value through the valid normative NIC 36 to measure the incidence that cause in the financial statements in San Ramón quarry in the period 2018. The methodology, which was used, was the quantitative approach, documentary type and field that allowed collecting and apply the technical process of the NIC 36 in deterioration of the value of assets of the San Ramón quarry, where the data were analyzed of numerical character, accounting of the actives, its accumulated depreciation, the recoverable amount, the amount in accounting books, asset flow and the obtained results of the accounting and financial information. It concludes that there is deterioration in the four machineries, generating economic losses to the quarry for a value of $62.226, 58, in a negatively affecting in the financial statements of the 2018 exercise mainly reflecting in the utilities. It is recommended that it be stabled periodically the fair value to assets, calculating the useful life, the real loss due to the deterioration of its value, the accounting bookkeeping and the determination of the real value of the machinery.